Analisis Informasi Citra MRI Genu Potongan Aksial antara Sekuen Short TAU Inversion Recovery (STIR) dan Sekuen T2-Spectral Attenuation Inversion Recovery (T2-SPAIR) - Thuthit Dwi Astuti; Emi Murniati; Sri Mulyati (Jurnal Imejing Diagnostik (JImeD), 2016)
Backgrounds: Genu MRI examination, according to Moeller (2003) and Westbrook (2008), was done by one fat supression technique in every slice. Radiology Installation of PAU dr.S.Hardjolukito Yogyakarta Hospital used two types of fat suppression technique those are STIR and T2-SPAIR. This study aims to find out the image differences between STIR and T2-SPAIR and to determine the fat suppresion technique that produces better image information of axial genu MR imaging.Methods: This research was a quantitative research with an experimental approach. Subjects of this study was image of axial genu MRI examination between STIR and T2- SPAIR in Radiology Installation of PAU dr.S.Hardjolukito Yogyakarta Hospital. The axial genu MR imaging STIR and T2-SPAIR assessed by three radiology phisicians using questioner. Data were statistically analyzed using Wilcoxon Sign Test.Results: The results showed a significant difference in all categories of assessment criteria between STIR and T2-SPAIR. In this study, the T2-SPAIR fat suppression technique produced better image information than STIR, whereas T2-SPAIR fat suppress signals was stronger than STIR.Conclusion: T2-SPAIR fat suppress signal was stronger than STIR that showed better image information and shorter time scanning